A social and economic history of the African people of Gcalekaland, 1830-1913 (Historia, 2021)
This article examines the history of the people of Gcalekaland from the nineteenth century to the early twentieth century. Primacy is given to factors which led to abject poverty and the subjection of the Gcaleka kingdom by the colonial governing authorities, such as the social and economic consequences of the wars of dispossession; the interference of the colonial government and the missionaries in the relations between amaGcaleka and amaMfengu; the rinderpest of 1896-97; the South African War of 1899-1902; and the Natives Land Act of 1913. All these factors contributed to the demise of the House of Gcaleka.  'n Sosiale en eknonomiese geskiedenis van die Afrikane van Gcalekaland, 1830-1913 Hierdie artikel ondersoek die geskiedenis van die Gcalekaland se mense vanaf die negentiende eeu tot die vroeër deel van die twintigste eeu. Die fokus val op die faktore wat tot kruipend armoede en die onderdanigheid van die Gcaleka koningryk deur die koloniale regering gelei het, soos die sosiale en ekonomiese gevolge van die oorloë van onteining; die tussenkoms van die koloniale regering en die sendelinge in die verwantskap tussen amaGcaleka en amaMfengu; die runderpes van 1896-97; die Suid-Afrikaanse Oorlog van 1899-1902; en die "Wet of Naturellegrond" van 1913. Hierdie faktore het tot die ondergand van die Huis van Gcaleka bygedra.
Keywords: Rinderpest; AmaMfengu; Nciba River; Abject poverty; Volslae armoede